The Role of Rhizobial ACC Deaminase in the Nodulation Process of Leguminous Plants - Francisco X. Nascimento; Clarisse Brígido; Bernard R. Glick; Márcio J. Rossi (International Journal of Agronomy, 2016)
Symbiotic rhizobia-legumes associations are extremely important in terms of sustainable agricultural practices. This symbiosis involves a complex interaction between both partners, plant and bacterium, for bacterial infection and the formation of symbiotic N-fixing nodules. In this regard, the phytohormone ethylene plays a significant role in nodule formation, acting as an inhibitor of the nodulation process. Ethylene not only regulates nodule development but also regulates many other plant developmental cues, including various stress responses that inhibit overall plant growth. Some rhizobia produce the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase, thus, being able to decrease ACC and, consequently, decrease deleterious ethylene levels that affect the nodulation process. This occurs because ACC is the immediate precursor of ethylene in all higher plants. Hence, rhizobia that express this enzyme have an increased symbiotic potential. In addition to the direct role that ACC deaminase plays in the nodulation process per se, in a limited number of instances, ACC deaminase can also modulate nodule persistence. This review focuses on the important role of rhizobial ACC deaminase during the nodulation process, emphasizing its significance to legume growth promotion.